Active exoskeleton reduces erector spinae muscle activity during lifting - Walter, Tobias; Stutzig, Norman; Siebert, Tobias (Frontiers in Bioengineering and Biotechnology, 2023)
Musculoskeletal disorders (MSD) are a widespread problem, often regarding the lumbar region. Exoskeletons designed to support the lower back could be used in physically demanding professions with the intention of reducing the strain on the musculoskeletal system, e.g., by lowering task-related muscle activation. The present study aims to investigate the effect of an active exoskeleton on back muscle activity when lifting weights. Within the framework of the study, 14 subjects were asked to lift a 15 kg box with and without an active exoskeleton which allows the adjustment of different levels of support, while the activity of their M. erector spinae (MES) was measured using surface electromyography. Additionally, the subjects were asked about their overall rating of perceived exertion (RPE) during lifting under various conditions. Using the exoskeleton with the maximum level of support, the muscle activity was significantly lower than without exoskeleton. A significant correlation was found between the exoskeleton’s support level and the reduction of MES activity. The higher the support level, the lower the observed muscle activity. Furthermore, when lifting with the maximum level of support, RPE was found to be significantly lower than without exoskeleton too. A reduction in the MES activity indicates actual support for the movement task and might indicate lower compression forces in the lumbar region. It is concluded that the active exoskeleton supports people noticeably when lifting heavy weights. Exoskeletons seem to be a powerful tool for reducing load during physically demanding jobs and thus, their use might be helpful in lowering the risk of MSD.